Hablemos de Historia de la Educación - Herrero Alejandro; Juan Bustamante Vismara; Patricia Cardona Zuloaga; Carlos Escalante Fernández; Antonio Espinoza; Flavia Fiorucci; Gerardo Garay Montaner; Laura S. Guic; Laura Graciela Rodríguez; Isidora Salinas Urrejola; Pablo Ariel Scharagrodsky; Pablo Toro-Blanco; et al. (Perspectivas Metodológicas​)
I'm interested in history. However, in my academic career I limited it to what is called the history of ideas, political history and history of education. I am concerned and occupied like any historian by the preservation of documentary archives and the very creation of sources. I find it very revealing to know the experience of the kitchen itself of research, teaching, modes of reading and various writing strategies. I believe that having made reports, surveys and questionnaires to colleagues in the scientific field and university education synthesizes the three concerns that have always been with me.